2014
DOI: 10.4028/www.scientific.net/amr.889-890.546
|View full text |Cite
|
Sign up to set email alerts
|

Motion Performance Analysis of Deep Water Pipe-Laying Vessel in Regular Wave

Abstract: Based on 3-D potential flow theory, sources and sinks are brought in, distributed upon the wet surface of ship hull. Three-dimensional non-speed frequency domain Green function is also introduced to determine the flow field velocity potential. As a result, added mass, damping coefficient and ship motion response of this deep water pipe-laying vessel are calculated under the regular wave condition. After compared these calculation results to model tank test data, we can see that the theoretical calculation fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Regarding the motion research of offshore platforms, threedimensional potential flow theory is one of the theories frequently used to analyze hydrodynamic performance [13]. Zan et al [14] calculated the additional mass, damping coefficient, and ship motion response of a deepwater-pipeline-laying ship under the condition of regular waves by utilizing three-dimensional potential flow theory and three-dimensional non-velocity frequency domain Green's function. Kristiansen et al [15] found, through experimental research on aquaculture equipment in waves and currents, that the wave-induced forces on the model were counteracted in many wave cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the motion research of offshore platforms, threedimensional potential flow theory is one of the theories frequently used to analyze hydrodynamic performance [13]. Zan et al [14] calculated the additional mass, damping coefficient, and ship motion response of a deepwater-pipeline-laying ship under the condition of regular waves by utilizing three-dimensional potential flow theory and three-dimensional non-velocity frequency domain Green's function. Kristiansen et al [15] found, through experimental research on aquaculture equipment in waves and currents, that the wave-induced forces on the model were counteracted in many wave cycles.…”
Section: Introductionmentioning
confidence: 99%